Penyuluhan Gizi Seimbang untuk Anak Sekolah Dasar di Panti Asuhan YARHIMA 4 Bondowoso - M Abd Nasir; Ciplis Gema Qori’ah; Adhitya Wardhono; Bhim Prakoso; Valda Sari Nurhandini; Aditya Alif Firmansya; Alicia Zalwa Julian; Nur' Imami Barokhatus Sholehah; Keren Filosa Cahyani; Agung Nugroho Puspito (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
Balanced nutrition refers to daily dietary composition containing appropriate types and amounts of nutrients required by the body. A balanced dietary pattern establishes healthy eating habits through adequate intake of carbohydrates, proteins, fats, vitamins, and minerals. Children frequently experience nutritional deficiencies and possess limited knowledge about healthy food sources. A social project was implemented through educational outreach and interactive games to address stunting issues among children at Yarhima 4 Orphanage, Bondowoso. The activity was conducted over four days using various methods including nutrition education sessions, film reviews, and fun games. Materials covered balanced nutrition concepts and the